Peningkatan Kemampuan Menulis Cerpen Melalui Model Pembelajaran Berbasis Masalah Pada Siswa Kelas IX C SMP Negeri 13 Magelang Tahun Pelajaran 2022/2023 - Isjulianti, Ester (Science and Education Journal (SICEDU), 2024)
This research aims to: (1) Describe the process of implementing a problem-based learning model in improving short story writing skills in class 9C students at SMP Negeri 13 Magelang. (2) Describe the level of short story writing ability of students at SMP Negeri 13 Magelang after implementing the problem-based learning model. This research is Classroom Action Research which consists of 2 cycles, each cycle consisting of 3 stages, namely: Planning, Action and Observation, and Reflection. The research subjects were 32 students in class 9C of SMP Negeri 13 Magelang. Data collection in this research used observation sheets and teacher performance assessment sheets. The data analysis techniques used are qualitative descriptive and quantitative descriptive. Based on the results of the research, of the 32 students who were the research subjects for the pre-cycle test results, only 8 students completed, namely the percentage who completed was 25% while those who did not complete were 75%, accumulatively, the average achievement score was 75.22. In Cycle I, the level of short story writing results for class 9C students at SMP Negeri 13 Magelang after implementing learning using the problem-based learning model in cycle I was 79.59 on average, after cycle II the average was 84.40. These results show that the application of learning with a problem-based learning model can improve the ability to write short stories in class IX C students at SMP Negeri 13 Magelang for the 2022/2023 academic year.